(untitled) (International Journal of Engineering and Computer Science, 2014)
Dental Biometric is mainly used in Forensic Science. Segmentation plays a vital role in the interpretation of Dental Radiograph that is useful in identification of an individual, bite mark analysis and in mass disasters. In this paper, we have an overview of a different discontinuities and Edge Detection Techniques. We have also done a comparative study of the edge detectors. In this Study, the first step we have done is pre-processing on animage. In the second step, we enhance the image by using Low Pass Filter and in the last step we applied different Edge Detectors on the image.